2017
DOI: 10.1080/10495398.2017.1297719
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Diversity, Population Structure, and Relationship Between Legendary Vechur Cattle and Crossbred Cattle of Kerala State, India

Abstract: The legendary Vechur cattle of Kerala, described as a very short breed, and the crossbred (CB) Sunandini cattle population exhibited great phenotypic variation; hence, the present study attempted to analyze the genetic diversity existing between them. A set of 14 polymorphic microsatellites were chosen from FAO-ISAG panel and amplified from genomic DNA isolated from blood samples of 30 Vechur and 64 unrelated crossbred cattle, using fluorescent labeled primers. Both populations revealed high genetic diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
1
7
3
Order By: Relevance
“…The H E mean value of 0.75 observed in the current study was lower than the 0.92 observed in Vechur cattle in India (Radhika et al 2018). The H O values ranged between 0.56 and 0.70, with a mean value of 0.66, and this was higher than 0.52 observed in Lidia bovine breed in Spain (Canon et al 2008), but lower than the value of 0.67 for Nguni cattle populations in Mozambique (Bessa et al 2009) and the value of 0.69 for Kankrej Cattle in India (Sodhi et al 2007).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The H E mean value of 0.75 observed in the current study was lower than the 0.92 observed in Vechur cattle in India (Radhika et al 2018). The H O values ranged between 0.56 and 0.70, with a mean value of 0.66, and this was higher than 0.52 observed in Lidia bovine breed in Spain (Canon et al 2008), but lower than the value of 0.67 for Nguni cattle populations in Mozambique (Bessa et al 2009) and the value of 0.69 for Kankrej Cattle in India (Sodhi et al 2007).…”
Section: Discussioncontrasting
confidence: 90%
“…It was observed that there was a higher genetic variation within individuals in the population (79%) than among populations (10%) or among individuals (11%). These low levels of differentiation among populations suggested common historical origins and a high level of inter-population gene flow (Radhika et al 2018). These findings are in line with Groeneveld et al (2010), who stated that most of the genetic diversity is present within a breed and not among breeds.…”
Section: Discussionsupporting
confidence: 81%
“…Breeds like Umblachery, Vechur, Ongole and Bargur showed mean F IS greater than 7% indicating significant heterozygosity deficit, possibly due to close breeding and potential inbreeding. The mean F IS for Vechur and Ongole cattle observed in the present study was significantly lower than reported previously by Radhika et al [ 28 ] and Sharma et al [ 26 ] respectively. The test for Hardy-Weinberg equilibrium (HWE) was conducted on a total of 378 breed X locus combinations.…”
Section: Resultscontrasting
confidence: 85%
“…However, the mean F IS estimates reported for West-Central Indian cattle were much higher than that of South Indian cattle (Shah et al 2012). Similarly, the mean F IS for Vechur and Ongole cattle observed in the present study was significantly lower than reported previously by Radhika et al (2018) and Sharma et al (2015) Figure SF1). Of these, HEL5 exhibited significant heterozygosity deficit and consequent deviation from HWE in 12 out of 14 studied populations.…”
Section: Basic Diversity Measures and Hardy-weinberg Equilibriumcontrasting
confidence: 60%